2022
DOI: 10.3389/fpubh.2022.850533
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Fatigue and Falls Risk Among the Elderly Aged Over 75 Years in China: The Chain Mediating Role of Falls Efficacy and Lower Limb Function

Abstract: BackgroundAlthough fatigue has been shown to be strongly associated with falls risk, very few studies have focused on its mechanism involved in community-dwelling older subjects. The purpose of this study was to explore the relationship between fatigue and falls risk and its internal mechanism by constructing a chain mediation model.MethodsA cross-sectional study design was adopted. A convenience sample of 270 older adults was recruited from July to October 2021 in an urban community, in Beijing, China. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…13 Additionally, fatigue can cause patients with sepsis to be at risk of falls 29 because it can impact lower limb function. 30 In our study, the incidence of a fall was not a major symptom experienced nor the primary cause for older adults with sepsis to visit the ED. However, previous studies found that falls were the most frequent cause of ED admission.…”
Section: Symptoms and Signs Of Sepsis Presentationmentioning
confidence: 54%
“…13 Additionally, fatigue can cause patients with sepsis to be at risk of falls 29 because it can impact lower limb function. 30 In our study, the incidence of a fall was not a major symptom experienced nor the primary cause for older adults with sepsis to visit the ED. However, previous studies found that falls were the most frequent cause of ED admission.…”
Section: Symptoms and Signs Of Sepsis Presentationmentioning
confidence: 54%
“…Being able to identify and monitor patterns of activities could inform self-management strategies. Fatigue also has a strong correlation with the risk of falls particularly with older individuals [10]. IoT-enabled smart healthcare can be used for the detection of falling events [11].…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, endeavors aiming to empower older people to prevent and manage falls need a clear understanding of falls efficacy. Some articles featured in the Frontiers have demonstrated these efforts, such as presenting the mediating role of falls efficacy between fatigue and falls risk (He et al, 2022 ) and the role of a falls risk-reduction program on falls efficacy (Cho et al, 2014 ). Given the advances in research on falls efficacy, have we adequately understood this self-efficacy concept and have the most appropriate measure applied for the construct of interest?…”
Section: Introductionmentioning
confidence: 99%